Advances in 3D/4D printing of mechanical metamaterials: From manufacturing to applications. (1st April 2023) - Zhou, Xueli; Ren, Luquan; Song, Zhengyi; Li, Guiwei; Zhang, Jifeng; Li, Bingqian; Wu, Qian; Li, Wangxuan; Ren, Lei; Liu, Qingping
Abstract: Mechanical metamaterials are a class of functional materials with designability and extraordinary mechanical properties. Due to the manufacturing limitation of traditional technology, most of the current research on mechanical metamaterials is limited to theoretical and simulation analysis. In recent years, the rapid development of 3D printing technology has provided an important means for the manufacturing of mechanical metamaterials with complex structures. In addition, the further combination with the 4D printing of smart materials is providing a boost to the development of smart programmable mechanical metamaterials. Here, we outline the recent advances in 3D/4D printing of mechanical metamaterials. First, 3D printing techniques for single-material, multi-material, and composite materials applicable to mechanical metamaterial manufacturing are discussed. Then, the structures and designs of several common mechanical metamaterials in 3D printing are summarized, including the 4D printing of smart programmable mechanical materials, and the applications of 3D/4D printing of mechanical metamaterials are presented. Finally, the future research prospects and challenges of 3D/4D printed mechanical metamaterials are foreseen.